On Some Estimate for the Norm of an Interpolation Projector - Mikhail V. Nevskii (Моделирование и анализ информационных систем)
Let $Q_n=[0,1]^n$ be the unit cube in ${\mathbb R}^n$ and let $C(Q_n)$ be a space of continuous functions $f:Q_n→{\mathbb R}$ with the norm $\|f\|_{C(Q_n)}:=\max_{x\in Q_n}|f(x)|.$ By $Π_1\left({\mathbb R}^n\right)$ denote a set of polynomials in $n$ variables of degree $≤ 1$, i. e., a set of linear functions on ${\mathbb R}^n$. The interpolation projector $P:C(Q_n)→ Π_1({\mathbb R}^n)$ with the nodes $x^{(j)}\in Q_n$ is defined by the equalities $Pf\left(x^{(j)}\right)= f\left(x^{(j)}\right)$, $j=1,$ $…,$ $ n+1$. Let $\|P\|_{Q_n}$ be the norm of $P$ as an operator from $C(Q_n)$ to $C(Q_n)$. If $n+1$ is an Hadamard number, then there exists a non-degenerate regular simplex having the vertices at vertices of $Q_n$. We discuss some approaches to get inequalities of the form $||P||_{Q_n}≤ c\sqrt{n}$ for the norm of the corresponding projector $P$.